Potential Role of Hepatozoon canis in a Fatal Systemic Disease in a Puppy - Andrea De Bonis (Pathogens, 2021)
Canine hepatozoonosis caused by Hepatozoon canis is an emerging disease in Europe. Clinical pictures vary from subclinical to life-threatening and non-specific clinical signs are predominantly reported. A 2-month-old female puppy originating from Southern Italy was adopted and moved to Northern Italy. Then, the dog was brought to a local veterinary practice for gastrointestinal signs, migrating lameness and pruritic dermatitis, and then tested positive for Hepatozoon spp. gamonts at the blood smear. After treatment with imidocarb dipropionate and doxycycline, the dog showed an initial clinical improvement. However, gastrointestinal signs recurred, and diffuse superficial pyoderma appeared on the thoracolumbar region, along with fever, lethargy, and weight loss. Eight months from the first onset of clinical signs, the dog was referred to a veterinary clinic and subjected to complete blood count, urine and fecal analysis, along with abdominal ultrasonography, whole-body CT and gastroduodenal endoscopy. Skin biopsies and blood samples were subjected to a PCR-coupled sequencing protocol, which scored both positive for H. canis. Alterations were consistent with a pre-existing cholangiohepatitis and multiple acquired extrahepatic shunts secondary to portal hypertension. The dog was euthanatized due to a clinical worsening two months later. The potential role of H. canis in the systemic disease observed, clinic-pathological findings and epizootiological implications are discussed.